ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.N DI WILAYAH PUSKESMAS PEKAUMAN BANJARMASIN - Aisyah, Putri; Ari Lestari, Nur Cahyani (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
According to the SDGs (Sustainable Development Goals) Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia. Based on the maternal mortality target from 2020 to August, there were 16 maternal deaths = (91.45/100,000), 27 maternal deaths = (227.22/100,000) the causes of death were bleeding, preeclampsia and comorbidities. 2020 to August there were 74 cases of infant mortality = (6.23/1,000), 116 post-infant deaths = 9.78/1,000) the causes of death were low birth weight, asphyxia and congenital abnormalities (Dinkes, RI 2020).The final project is implementing comprehensive midwifery care Antenatal Care (ANC), Intranatal Care (INC), Postnatal Care (PNC), Neonates and Family Planning to Ny. N with mild anemia. The final project is prepared in the form of a case study of Mrs. N is 30 years old, 35 weeks of gestation, Varney's midwifery management approach, documentation of SOAP in the Pekauman Health Center area of Banjarmasin on 26 October 2020 to 5 January 2021.